THE QUALITATIVE STUDY OF NCP IN HOSPITAL HOPE AND PRAYER OF BENGKULU CITY - Putra, Deri Andika (JPP JURNAL KESEHATAN POLTEKKES PALEMBANG, 2021)
Background. Nutrition care practices that do not meet hospital standards cause several barriers to the needs and preferences of each patient. One of the obstacles often faced by hospitals in efforts to cure patients. The research objective is to get an overview of the role of internal and external factors in the application of nutrition care process (NCP) at the Hope and Prayer Hospital of Bengkulu City. Method. Qualitative research with a Phenomelogy approach. Phenomenology is a method carried out by researchers to find out phenomena that occur naturally. The phenomenological method emphasizes human experience and how humans interpret their experiences. Results. The process of nutrition care process (NCP) that has not been carried out optimally. In the process of implementing a dietitious NCP expect improvement in the work system between health workers and simplification of the NCP system in hospitals, and not being spared dietitically expects to be supported by hospital policies that do not burden dietitics. Conclusion. Internal factors in implementing NCP are already good, in terms of knowledge and work motivation. External factors, there are several issues regarding collaborative work among health workers in the form of authority and responsibilities as well as confusing hospital policies.